The role of AMPA receptors in postsynaptic mechanisms of synaptic plasticity - Chater, Thomas E.; Goda, Yukiko (Frontiers in Cellular Neuroscience, 2014)
In the mammalian central nervous system, excitatory glutamatergic synapses harness neurotransmission that is mediated by ion flow through AMPA receptors. AMPARs, which are enriched in the post-synaptic membrane on dendritic spines, are highly dynamic, and shuttle in and out of synapses in an activity-dependent manner. Changes in their number, subunit composition, phosphorylation state, and accessory proteins can all regulate AMPARs and thus modify synaptic strength and support cellular forms of learning. Furthermore, dysregulation of AMPAR plasticity has been implicated in various pathological states and has important consequences for mental health. Here we focus on the mechanisms that control AMPAR plasticity, drawing particularly from the extensive studies on hippocampal synapses, and highlight recent advances in the field along with considerations for future directions.